COWORKING SPACES AND SKILLS FOR CONSTRUCTIVE WORK IN THEM - Pocevičienė, Rasa; Gavėnavičienė, Rūta (PROFESSIONAL STUDIES: Theory And Practice, 2022)
Constant change in all spheres of life, new challenges for humanity, and at the same time new opportunities to overcome them, rapidly evolving ICT, the increasing use of artificial intelligence, even in areas traditionally associated only with direct human participation and action. Naturally, all this is changing, and will change even more in the future, not only the nature of work and activities, but also the environments and spaces in which those activities take place. One such environment / space is the coworking space. Coworking is the new path of melding life and work in a sustainable fashion. It is the global linchpin at the intersection of real estate, technology and community, which will shape the way we work in the future. Although the advantages of coworking spaces have been repeatedly mentioned in both practical and theoretical discourse, there is still little in-depth research on this phenomenon, especially on what skills are needed for constructive and successful work in them and what role higher education institutions should play in this context in educating a new generation of managers and entrepreneurs. Keywords: coworking, coworking space, business administration, self-directed learning and working competencies, communication, collaboration.